An exact series solution for the vibration analysis of cylindrical shells with arbitrary boundary conditions - Dai, Lu; Yang, Tiejun; Du, Jingtao; Li, W. L.; Brennan, M. J. [UNESP] (My University, 2013)
In this paper, an exact series solution for the vibration analysis of circular cylindrical shells with arbitrary boundary conditions is obtained, using the elastic equations based on Flügge's theory. Each of the three displacements is represented by a Fourier series and auxiliary functions and sought in a strong form by letting the solution exactly satisfy both the governing differential equations and the boundary conditions on a point-wise basis. Since the series solution has to be truncated for numerical implementation, the term exactly satisfying should be understood as a satisfaction with arbitrary precision. One of the important advantages of this approach is that it can be universally applied to shells with a variety of different boundary conditions, without the need of making any corresponding modifications to the solution algorithms and implementation procedures as typically required in other techniques. Furthermore, the current method can be easily used to deal with more complicated boundary conditions such as point supports, partial supports, and non-uniform elastic restraints. Numerical examples are presented regarding the modal parameters of shells with various boundary conditions. The capacity and reliability of this solution method are demonstrated through these examples. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Cylindrical shell; Elastically restrained edge; Exact series solution; Improved Fourier series method; Vibration; Elastically restrained edges; Fourier series method; Series solutions; Cylinders (shapes); Fourier series; Modal analysis; Shells (structures); Vibration analysis; Boundary conditions